Pengembangan LKS Berbasis Project Based Learning untuk Meningkatkan Keterampilan Proses Sains Siswa SMP - Fajriyanti, Zaro'ah Dwi; Ernawati, Tias; Sujatmika, Sigit (Science Education Programme Study, IKIP Veteran Semarang, 2018)
Penelitian ini bertujuan untuk: 1) menghasilkan Lembar Kerja Siswa (LKS) berbasis Project Based Learning (PjBL) pada materi konsep energi  dan sumber energi guna meningkatkan keterampilan proses sains siswa kelas VII SMP, 2) mendeskripsikan kualitas LKS berbasis PjBL yang dikembangkan. Penelitian ini termasuk penelitian pengembangan dengan model pengembangan 4D. Teknik pengumpulan data menggunakan instrumen penilaian untuk beberapa reviewer. Teknik analisis data menggunakan analisis kualitas LKS. Berdasarkan penilaian dosen ahli, peer reviewer, dan guru IPA diperoleh skor rata-rata 141,9 dengan persentase keidealan 81,1% menyatakan bahwa kualitas LKS Sangat Baik. Hasil tanggapan siswa diperoleh skor rata-rata 75 dengan persentase keidealan 88,2% menyatakan bahwa kualitas LKS Sangat Baik. Dapat disimpulkan bahwa LKS yang dikembangkan layak digunakan dalam pembelajaran. Developing The Student’s Worksheet Based on Project Based Learning to Improve Student Science Process Skills on Junior High School Abstract This research was aimed to: 1) produced a student’s worksheet based on project based learning on concept of energy and energy resources material to improve he student’s science process skills in seven grade of Junior High School, 2) described the quality of student’s worksheet based on project based learning was developed. This research is include research and development with 4D models. Data collection technique used  assessment instrument for reviewers. Data analysis technique used analysis quality of student’s worksheet. According to assessment of expert lecturer, peer reviewer, and natural science teacher got an average score of 141,9 with ideal presentage of 81,1% stated that the quality of student’s worksheet was very good. The result of students respons got an average score of 75 with ideal percentage of 88,2% stated that the quality of student’s worksheet was very good. In conclusion that the student’s worksheet had been developed was feasible to implement on the lesson.